Epidemics and history : disease, power, and imperialism - Watts, S. J. (Sheldon J.) (Yale University Press, 1997)
This book will become the standard account of the way disease has transformed societies and of how the structuring of society, politics, the economy and the medical profession has shaped the spread and containment of epidemics.